Struktur Populasi, Frekuensi Kasus Penyakit dan Respon Antibodi pada Sapi Lokal dan Kerbau Pampangan Pascavaksinasi Septicaemia Epizootica di Kabupaten Ogan Komering Ilir, Sumatera Selatan - Aksi; Mudawamah; Badat Muwakhid (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to analyze population structure, disease case frequency, and post-vaccination antibody responses of Pampangan cattle and buffalo following Septicaemia Epizootica (SE) vaccination in Ogan Komering Ilir (OKI) Regency, South Sumatra. The research employed a quantitative longitudinal observational design based on secondary data collected from March to August 2024, including livestock population records, disease cases, vaccination coverage, and antibody test results measured using the ELISA method. Data were analyzed descriptively and inferentially through normality tests, independent t-tests, Mann–Whitney U tests, Chi-Square tests, and Kruskal–Wallis tests according to data distribution. The results indicated significant to highly significant differences in population structure between cattle and buffalo. Cattle populations were higher in total number (35,999 vs. 10,297 head), proportion of calves (17.48% vs. 14.54%) and young stock (25.05% vs. 23.25%), male–female ratio (66.38% vs. 62.03%), and replacement rate (40.61% vs. 38.79%). In contrast, buffalo showed higher proportions of adult animals (62.21% vs. 57.47%), breeding herd (38.84% vs. 35.75%), and potential dams (53.90% vs. 50.26%). Nevertheless, both cattle and buffalo met national standards for sex ratio and replacement indicators. The frequency of SE cases did not differ significantly between species; however, descriptively, increased vaccination coverage was associated with a decline in reported cases. Post-vaccination antibody responses were not significantly influenced by species, breed, or geographical area. In conclusion, SE vaccination proved effective in reducing disease spread and generating consistent immunity across livestock, despite existing differences in population structure.